ANALISA TEKNIS OPTIMALISASI SISTEM PROPULSI KAPAL IKAN MENGGUNAKAN CVT GEARBOX - Eko Prayitno, Muhamad Muhadi (Department of Naval Architecture - Diponegoro University, 2012)
The propulsion system of traditional fishing vessels until this time generally still using a single transmission gearbox. Transmission system with a single speed gearbox cannot operate at the optimum operation main engine, causing the engine operation is unefficient. To obtain the optimum operational of propulsion system is carried out loading curve analysis method using ANLOVA software and engine propeller matching. Calculation of ship resistance using Maxsurf with Ootmerssen method and DelfIII. The calculation result of ship resistance using both method is analyzed to obtain constraints on the ship accordance with the LSE method. The analysis of matching engine propeller data obtained from CVT gearbox ratios setting in the range of 5 to 9. The impact of setting the ratio obtained the spesific fuel consumption reduction of 6gram/kw/h or 720 gram/hour at speed of 7 knot, meanwhile the highest fuel consumption reduction obtained at the point of operation of 5:48 speed knots with a decrease spesific fuel consumption 21 gram/kW/h or 1260 grams/hour.